POTENTIAL HUMAN EXPOSURE TO MERCURY (HG) IN A CHLOR-ALKALI PLANT IMPACTED ZONE: RISK CHARACTERIZATION USING UPDATED SITE ASSESSMENT DATA - Kismelyeva, Symbat; Khalikhan, Rustem; Torezhan, Aisulu; Kumisbek, Aiganym; Akimzhanova, Zhanel; Karaca, Ferhat; Guney, Mert (MDPI, 2021)
Industrial activities have resulted in severe environmental contamination that may expose rural and urban populations to unacceptable health risks. For example, chlor-alkali plants (CAPs) have historically contributed mercury (Hg) contamination in different environmental compartments. One such site (a burden from the Soviet Union) is located in an industrial complex in Pavlodar, Kazakhstan. Earlier studies showed the CAP operating in the second half of the twentieth century caused elevated Hg levels in soil, water, air, and biota. However, follow-up studies with thorough risk characterization are missing. The present study aims to provide a detailed risk characterization based on the data from a recent site assessment around the former CAP. The ⅀HI (hazard index) ranged from 9.30 × 10−4 to 0.125 (deterministic method) and from 5.19 × 10−4 to 2.54 × 10−2 (probabilistic method). The results indicate acceptable excess human health risks from exposure to Hg contamination in the region, i.e., exposure to other Hg sources not considered. Air inhalation and soil ingestion pathways contributed to the highest ⅀HI values (up to 99.9% and 92.0%, respectively). The residential exposure scenario (among four) presented the greatest human health risks, with ⅀HI values ranging from 1.23 × 10−2 to 0.125. Although the local urban and rural population is exposed to acceptable risks coming from exposure to Hg-contaminated environmental media, an assessment of contamination directly on the former CAP site on the industrial complex could not be performed due to access prohibition. Furthermore, the risks from ingesting contaminated fish were not covered as methyl-Hg was not targeted. An additional assessment may be needed for the scenarios of exposure of workers on the industrial complex and of the local population consuming fish from contaminated Lake Balkyldak. Studies on the fate and transport of Hg in the contaminated ecosystem are also recommended considering Hg methylation and subsequent bioaccumulation in the food chain.
Keywords: exposure assessment; heavy metals; Kazakhstan; Pavlodar; water pollution; risk assessment; Type of access: Open Access; soil pollution